2011
DOI: 10.1002/jcp.22728
|View full text |Cite
|
Sign up to set email alerts
|

Histone acetylation is essential for ANG‐II‐induced IGF‐IIR gene expression in H9c2 cardiomyoblast cells and pathologically hypertensive rat heart

Abstract: The IGF-II/mannose 6-phosphate receptor (IGF-IIR/Man-6-P) up-regulation correlates with heart disease progression and its signaling cascades directly trigger pathological cardiac hypertrophy, fibrosis, and cardiomyocytes apoptosis. IGF-IIR gene expression/ suppression is able to prevent myocardial remodeling. However, the regulating mechanisms for the IGF-IIR gene remain unclear. This study performed reverse transcriptase PCR (RT-PCR) and methylation-specific PCR (MS-PCR) to detect expression and DNA methylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 41 publications
2
29
0
Order By: Relevance
“…These findings support our previous studies. 10,14,29 We also observed that other kinases downstream of AT 1 R were involved in IGF-IIR expression. However, these kinases may have influenced IGF-IIR expression via different mechanisms, such as protein stability and degradation.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…These findings support our previous studies. 10,14,29 We also observed that other kinases downstream of AT 1 R were involved in IGF-IIR expression. However, these kinases may have influenced IGF-IIR expression via different mechanisms, such as protein stability and degradation.…”
Section: Discussionmentioning
confidence: 59%
“…14 ANG II has been reported to activate downstream signaling via the angiotensin type 1 and type 2 receptors (AT 1 R and AT 2 R, respectively) to elicit various biological responses. 1,2 As shown in Figure 1a, the knockdown of AT 1 R reduced the upregulation of IGF-IIR expression by ANG II, whereas the knockdown of AT 2 R had no obvious influence on IGF-IIR regulation by ANG II.…”
Section: Resultsmentioning
confidence: 99%
“…32 After the demethylation of H3K27me3, Sp1 that is recruited to the promoter may lead to positive regulation of the Nkcc1 gene with co-activators such as histone acetyltransferases in hypertensive rats. Although Ang II increased the histone acetylation for IGF-IIreceptor gene expression, 33 it is still not clear whether the upregulation of the Nkcc1 gene promoter activity is caused by indirect mechanisms downstream of Ang II, such as oxidative stress and high BP, or by a direct mechanism through the activation of Ang II receptors. This question is very substantial and should be resolved in a future study.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that Ang II increases acetyl-histone H3 and acetyl-histone H4 without affecting DNA methylation when it induces insulin-like growth factor type II receptor gene expression in H9c2 cardiomyoblast cells and pathologically hypertensive rat heart. 32 Thus, further studies will be needed to clarify the relevance of epigenetic changes in the development of cardiovascular disease, including hypertension. …”
Section: Lee Et Almentioning
confidence: 99%